Proniosomal Gel of Tretinoin for the Treatment of Acne Vulgaris - Anindita De and Amandeep Kaur Gill (Journal of Applied Pharmaceutical Science, 2013)
The objective of the present study was to formulate and evaluate Tretinoin proniosomal gel and to carry out comparative skin irritation study with conventional Tretinoin solution and Tretinoin conventional gel. Topical Tretinoin (0.25%, 0.05%) has been a reliable treatment of acne vulgaris since 30 years but its major drawback is that it causes skin irritation on the applied area. The proniosomal dispersion was prepared using different grades of non-ionic surfactants and cholesterol in different ratios along with Tretinoin. The scanning electron microscopy revealed that the proniosome vesicles were of LUV type and spherical shape. The proniosome vesicles prepared with SPAN 60, 40 and cholesterol in formulation PN9 showed maximum entrapment efficiency (76.77±1.54) .The prepared proniosome vesicles were incorporated into Carbopol gel (1%) base to prepare Tretinoin proniosomal gel. The stability study was carried out at different accelerated and non-accelerated conditions. The In-vitro diffusion study carried out using sigma dialysis membrane showed sustained release pattern of Tretinoin from proniosomal gel formulation. The comparative skin irritation study carried out on 18 healthy Wistar Rats of either sex showed remarkable decrease in signs of skin irritation caused by Tretinoin.
Keywords: Tretinoin, Acne, Proniosomes, Diffusion Study, Skin